1977
DOI: 10.1002/pssa.2210390202
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric power in reduced pure and Nb-doped TiO2 rutile at high temperature

Abstract: The nature of defects in reduced pure and Nb‐doped TiO2 rutile is investigated at high temperature by Seebeck coefficient measurements. The classical point defect model approach allows a good fit of the theoretical curves to experimental data. In undoped rutile, the main defects should be titanium interstitials in a large oxygen partial pressure range. For small departures from stoichiometry, the influence of impurities and band to band thermal excitation is discussed. In the case of Nb‐doped rutile, two kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 14 publications
5
101
1
Order By: Relevance
“…The formation of these defects have been already postulated before [5][6][7][8]. So far, however, the effects related to the formation of these defects were observed for TiO 2 single crystal only [4].…”
Section: Introductionmentioning
confidence: 92%
“…The formation of these defects have been already postulated before [5][6][7][8]. So far, however, the effects related to the formation of these defects were observed for TiO 2 single crystal only [4].…”
Section: Introductionmentioning
confidence: 92%
“…At intermediate temperatures, nominally undoped rutile single crystals are electronic conductors with very low ionic transference number. [ 27 ] In case of signifi cantly doped rutile the ionic transference number depends on p O 2 ; the number is negligible at very low and high p O 2 and increases at intermediate p O 2 . [ 29 ] Based on simple mass action laws and electroneutrality conditions, the defect concentrations can be related to the oxygen partial pressure ( p O 2 ) when equilibrium with gas phase is established: [ 28 ] …”
Section: Tem Characterizationmentioning
confidence: 98%
“…[ 12 , 15 ] In other studies the same slip systems were found. [ 19 , 20 ] The electrical properties of TiO 2 were studied independently in the past [27][28][29] in slightly and strongly reducing atmosphere where nominally undoped TiO 2 is an n-type conductor, and in oxidizing atmosphere where rutile is p-type conducting. At intermediate temperatures, nominally undoped rutile single crystals are electronic conductors with very low ionic transference number.…”
Section: Tem Characterizationmentioning
confidence: 99%
“…The thermoelectric power data for TiO 2 at elevated temperatures are scarce and limited to several reports [5][6][7][8]. Moreover, there is no consistency between the reported data.…”
Section: Introductionmentioning
confidence: 53%
“…While [5] these defects may assume different valencies, it has been generally assumed that the defect disorder at elevated temperatures consist predominantly of the following defects:…”
Section: Defect Disordermentioning
confidence: 99%